НУРМОН АБДУВОЙ ЎҒЛИ ВА УНИНГ САМАРҚАНД ДОСТОНЧИЛИГИ АНЪАНАСИДА ТУТГАН ЎРНИ - Худайқулова, Л. (SCIENCE and SOCIETY, 2021)
The article deals with the work of the famous national poet Nurmon Abduvoy oglu. He was distinguished by his extraordinary responsiveness and high level of artistic ability.
Keywords: epic tradition; epic; epic-bakhshi; epic "Kuntugmish"; variant